Good communication that blocks learning. - ARGYRIS, Chris (1994)
Shows how techniques of corporate communication such as focus groups and surveys discourage the kind of organisational self-examination that is necessary today. Concludes that managers need employees who think constantly and creatively about the needs of the organisation. The problem is not that employees run away from organisational self-examination, the problem is that no one asks it of them.